Asbestos and its diseases - Craighead, John E.; Gibbs, A. R. (New York ; Oxford : Oxford University Press, 2008)
This work covers geology and mineralogy, lung function testing, industrial and commercial hygiene, risk assessment, cellular and molecular interactions, epidemiology of human diseases, physiology, clinical features, regulatory approaches, and absestos litigation. It will be a useful resource for both health professionals and lawyers.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Asbestosis; Asbestos -- Toxicology; Asbestos -- Health aspects; Asbestos -- Carcinogenicity